Implications of Ethics in Law Enforcement on Medical Decisions - Hodijatussolihah; Hj. Yeti Kurniati; Hj. Hernawati RAS (Formosa Journal of Social Sciences (FJSS), 2023)
This study analyzes the interaction between medical ethics and law in the context of medical decisions involving ethical dilemmas. Through a cross-disciplinary approach, we explore the views of legal practitioners, medical professionals, and ethicists on the practical challenges of applying the law to sensitive medical decisions. We highlight differences in interpretation between various stakeholders in the ethical implications of law enforcement for medical decisions, while exploring collaborative efforts and recommendations to improve ethical and fair resolution